Biochemical study of antioxidants level in saliva and serum of obese individuals who have a family history of type II diabetes mellitus - Maha Amjaad Hameed; Rafah Razooq Hameed; Amina Hameed Obeidi (Tikrit Journal of Pure Science)
The study includes a comparative study  biochemical  comparative study  between the blood and saliva at some pointers early diagnosis for diabetes type II in obese people and over weight ,as this study was conducted on 150 sample (males and females) of  blood serum and saliva ,as she was the first set of blood serum of fat people with over  weight and they have not family history of second type ΙΙ diabetes obese and over weight people have a family history of diabetes.